OPTIMIZATION OF DIETARY ENERGY DENSITY FOR BROILER CHICKENS DURING THE COLD DRY SEASON OF JOS, PLATEAU STATE, NIGERIA - Idachaba, Collins Udagbene; Adeniyi, Adebayo Kunle; Oludayo, Akinsola Michael; Oladipo, Mary Foluke; Kurdor, Peter Nandur; Abdullahi, Idris; Zungum, Aliyu Garba (FUDMA Journal of Sciences, 2026)
This study evaluated the optimization of dietary energy density for broiler chickens during the cold dry season of Jos, Plateau State, Nigeria. A total of 210 Arbor Acre day-old broiler chicks were assigned to five dietary treatments in a completely randomized design with three replicates of fourteen birds each. Starter diets contained 3000, 3025, 3050, 3075 and 3100 kcal/kg ME in diets T1 to T5 respectively, with 23% CP in all diets. Finisher diets contained 3200, 3225, 3250, 3275, and 3300 kcal/kg ME in diets T1 to T5 respectively with 20% CP in all diets. Feed and water were provided ad libitum, growth indices and villi morphometry were evaluated. During the starter phase, birds fed 3075 kcal/kg ME achieved the highest (P<0.05) final body weight (1080.17 g/bird) and daily weight gain (1036.97 g/bird/day), with the best (P<0.05) FCR (1.40). Feed intake decreased from 1520.22 g/bird/day at 3000 kcal/kg to about 1450 g/bird/day at higher energy levels, while the lowest feed cost per kilogram gain (₦1280.40) was recorded at 3075 kcal/kg. During the finisher phase, birds fed 3275 kcal/kg ME recorded the highest final body weight (2750.38 g/bird) and best FCR (1.81), while the lowest feed cost per kilogram gain (₦1965.13) occurred at 3250 kcal/kg. Villus height increased from 980.32 µm at 3200 kcal/kg to 1180.46 µm at 3275 kcal/kg, with villus height-to-crypt depth ratio improving from 4.65 to 5.30. Mortality was 0.00% across treatments.